"Supply push" or "demand pull?": Strategic recommendations for the responsible development of biofuel in China. (December 2015) - Ren, Jingzheng; Dong, Liang; Sun, Lu; Evan Goodsite, Michael; Dong, Lichun; Luo, Xiao; Sovacool, Benjamin K.
Abstract: This study investigates China׳s biofuel industry—the third largest in the world—by combining a strength, weakness, opportunity and threats (SWOT) analysis with a method known as fuzzy analytic hierarchy process (FAHP). More specifically, the study employs SWOT analysis to identify the influential factors affecting the development of the biofuel industry in China. It then prioritizes their importance using the FAHP method. The study finds that high production costs, competition with other renewable energy resources, inconsistent policy and legislation support, and poor technical standards are impeding the growth of the biofuel industry of China. The study concludes by proposing strategic recommendations for how the industry can be made both leaner, more efficient and effective, and greener, more socially and environmentally sustainable. Some of these options focuses on improving technical perform, adhering to a "supply push" mentality. Others focus on improving affordability and consumer awareness, adhering to a "demand pull" mentality.